PENGARUH KEMAKMURAN PEMERINTAH DAERAH, UKURAN PEMERINTAH DAERAH, DAN TINGKAT KETERGANTUNGAN PEMERINTAH DAERAH TERHADAP KINERJA KEUANGAN PEMERINTAH KABUPATEN/KOTA DI PROVINSI ACEH - Rafika Aulia; Rahmawaty Rahmawaty (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This study aims to examine the effect of regional government prosperity, local government size, and regional dependency level government on the financial performance of districts/city governments in Aceh Province. The population of this research is all districts and cities in Aceh Province, that as many as 23 districts/city in 2014-2018. This study uses secondary data with data collection techniques documentation methods. Statistical tests are performed with multiple linear regression analysis using SPSS program version 23. The result of the research shown that the regional government prosperity and local government size affect the financial performance of local governments while the regional dependency level government has no effect on the financial performance of local governments.